Villa trading contract with right to use on timeshare business program in Bali - Sutrisni, Ni Ketut Elly (International research journal of management, IT and social sciences, 2018)
Ownership of villas by Foreigners is possible with the right to use (RTU) not property rights. And Foreign Citizen is domiciled in Indonesia according to Government Regulation No. 40 on Right of Use, Right of Use and Right to Use. The sale and purchase of villa with use rights in the Time Share program is a formal agreement, meaning that for the legal villa sale agreement is not solely achieved by the agreement between seller and buyer concerning goods and price only (consensual), but by Law, the specified formality. As for what is meant by certain formalities in buying and selling villa is a necessity to be conducted notarial. In the contract of sale and purchase of villa with use rights in the Time Share program, the arrangement of Force Majeure is explicitly not regulated, but this must be expressly stipulated in the sale and purchase agreement. In the agreement stated that the owner or management will provide replacement accommodation and the management has also insured villas so that if the villa is destroyed due to unforeseen circumstances, the insurer will take over the risk of various dangers that may occur.